The Malaysian health reform in primary health care services - I Aniza,; M Jamsiah,; S.A Amin,; M Ali,; A.M Munizam, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2008)
Introduction : Family Health Development Division is one of the earliest divisions in Public Health Department, Ministry of Health Malaysia. The division has progressed each year with the extension and expansion of the scopes of services since the establishment of Maternal and Child Health Unit in 1956. The services currently include school children, adolescent, adult and elderly health and also known as life-course perspective: from womb to tomb. Objectives : The objective is to elaborate and explain the reformation of primary health care services implemented in the past and present. Methods : The methodology applied is compilation, data review and comparison from annual report, action plan report, articles, speeches, specialists and stake holder view. Results : The focus of Primary Health Care Service is covering health promotion, disease prevention, early detection and treatment, acute disease care, disease limitation and rehabilitation, clinical support services and teleprimary care. The reformation is caused by factors such as globalization, modernization, growth of health market, emergence and re-emergence of diseases, and development of medical technology. Three health fields that have underwent and under going reformation are concept and wellness practise in primary healthcare, primary healthcare clinical support services development and primary healthcare informatics development. The outcome of these reformations is the increment of service quality and outstanding services for patients and health staffs. Conclusion : Health reformation in primary healthcare is greatly needed to give excellent services for primary health care for today and future.